Eksplorasi Media Loose Parts dari Bahan Alam Dalam Menstimulus Kreativitas Anak Usia Dini di Pos Paud Pelita Mandiri Kertek - Dina Zuhda Syauqia; Siti Rohmatun; Ani Sofiana Istiqomah; Fatiatun Fatiatun (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
Early Childhood Education (PAUD) is a stage of education that plays a crucial role in maximizing children's cognitive, social-emotional, motor skills, and creativity growth at their peak developmental stage. Children aged three to six learn efficiently through play, hands-on exploration, and interaction with their surroundings. The purpose of this study was to evaluate the use of loose parts media based on natural materials as a means to stimulate creativity in early childhood at PAUD Pelita Mandiri Kertek. This study adopted a descriptive qualitative approach and utilized data collection techniques such as observation, in-depth interviews with teachers, and documentation of children's work. The main focus of this study was on the use of various natural materials, such as corn cobs, twigs, pebbles, and leaves, in play and learning activities. The results showed that loose parts media using natural materials can enhance children's creativity by improving problem-solving skills, strengthening verbal skills in expressing ideas and telling stories about their work, and supporting independent learning because children are actively involved in the educational process. The open-ended nature of the materials allows children to explore and express their ideas freely, thus creating a learning atmosphere full of creativity, innovation, and fun. The implications of this research indicate that the use of loose parts media based on natural materials can be an alternative learning method that is not only effective, but also economical and easy to implement to support the development of children's creativity, independence, and thinking skills, in line with the principles of child-centered learning.